Monetary analysis: a VAR perspective - Dieter Gerdesmeier; Barbara Roffia (Frankfurt School of Finance & Management, 2007)
The purpose of this study is to investigate the dynamic relationships between some key variables for the euro area by means of a systems approach (i.e. so-called Vector Autoregression) and to simulate their responses with respect to monetary policy shocks. The main result is that rather simple models can provide plausible reactions to changes in monetary policy. In particular, a positive shock in the short-term nominal interest rate is followed by a transitory decline in real income as well as a negative and permanent effect on the price level and nominal M3, leaving real M3 broadly unchanged.
urn:nbn:de:101:1-20080827204
Keywords: E52; F21; 330; Monetary analysis; VAR models; generalized impulse response functions